Politeness Strategies and Levels In Tourism-Service Language in Surakarta Residency - Budi Purnomo (UIN Salatiga, 2010)
In tourism industry, tourists act as guests and tourism industry practitioners act as hosts. Typically tourism industry practitioners will try to act politely and follow politeness strategies as well as possible when serving tourists to ensure their satisfaction. Levels of satisfaction could be determined by the politeness of the hosts' behaviour towards their guests, including the politeness levels of their tourism-service language. This research was done in Surakarta Residency, the main tourist destination in Central Java. Data sources of this research came from (1) informants and (2) events. The data were analyzed by Brown and Levinson’s politeness strategies (1987). The results of this research show that the tourism industry practitioners in Surakarta Residency use various politeness strategies and levels in tourism-service language to serve their guests.keywords; Politeness Strategies; Politeness Levels; Tourism-Service Language